2010
DOI: 10.1016/j.jacc.2010.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)-Epicatechin on Myocardial Infarct Size and Left Ventricular Remodeling After Permanent Coronary Occlusion

Abstract: Objectives We examined the effects of the flavanol (−)-epicatechin on short and long-term infarct size and left ventricular (LV) structure/function after permanent coronary occlusion (PCO) and the potential involvement of the protective AKT/ERK signaling pathways. Background (−)-Epicatechin reduces blood pressure in hypertensive patients and limits infarct size in animal models of myocardial ischemia-reperfusion injury. However, nothing is known about its effects on infarction after PCO. Methods (−)-Epicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 47 publications
0
55
0
1
Order By: Relevance
“…It has been reported that EPI can reduce the mortality of CVD [29]. The protective effect of EPI may occur via a reduction in oxidative stress, and improvement of mitochondrial structure and function [15-17]. Previous studies have also revealed that EPI-rich cocoa treatment improved mitochondrial structure and enhanced cardiac and/or SkM muscle function in patients with heart failure [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that EPI can reduce the mortality of CVD [29]. The protective effect of EPI may occur via a reduction in oxidative stress, and improvement of mitochondrial structure and function [15-17]. Previous studies have also revealed that EPI-rich cocoa treatment improved mitochondrial structure and enhanced cardiac and/or SkM muscle function in patients with heart failure [18].…”
Section: Discussionmentioning
confidence: 99%
“…Epicatechin (EPI) is considered an important factor that may be responsible for the beneficial effects of these flavanol-rich foods [13, 14]. Pharmacological studies have found that EPI exhibits protective effects on oxidative stress injury, myocardial ischemia reperfusion injury and permanent coronary occlusion [15-17]. EPI treatment also improved mitochondrial structure in enhanced cardiac and/or SkM muscle function in patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that the activation of eNOS can exert cardioprotective effects (32,18) and thus, agents that stimulate its activity may be of therapeutic interest. In support of this, we recently reported on the cardioprotective effects of EPI on animals subjected to ischemiareperfusion or permanent coronary occlusion (35,36).…”
mentioning
confidence: 63%
“…Some animal studies demonstrate that (-)-epicatechin increases NO production in endothelial cells [78] and attenuates myocardial injury [79,80]. There are several studies showing that the NO pathway may play a role in mitochondrial biogenesis [81][82][83] and angiogenesis [84] in skeletal muscle.…”
Section: (-)-Epicatechinmentioning
confidence: 99%